Assessment of 4‐Aminoantipyrine Degradation and Mineralization by Photoelectro‐Fenton with a Boron‐Doped Diamond Anode: Optimization, Treatment in Municipal Secondary Effluent, and Toxicity. Issue 3 (7th February 2019) - da Silva, Lucas M.; Gozzi, Fábio; Cavalcante, Rodrigo P.; de Oliveira, Silvio C.; Brillas, Enric; Sirés, Ignasi; Machulek, Amilcar
Abstract: 4‐Aminoantipyrine (4‐AA), a persistent metabolite of dipyrone found in natural water, has been treated in 100 mL of aqueous 0.050 M Na2 SO4 solutions at pH 3.0 by photoelectro‐Fenton (PEF) with a 4 W UVA lamp. The assays were performed in a cell equipped with a boron‐doped diamond (BDD) anode and an air‐diffusion cathode for H2 O2 generation. The formation of an unstable Fe(III)‐4‐AA complex with 1 : 2 molar ratio was evidenced. A 2 4 central composite design was used to assess the effect of four independent variables on PEF performance. The optimized conditions for 62.5 mg L −1 4‐AA were: current density of 77.5 mA cm −2 and 47.75 mg L −1 Fe 2+, yielding 99 % 4‐AA degradation at 7 min, and 45 % 4‐AA mineralization with 3.2 % mineralization current efficiency at 130 min. Slightly slower degradation and similar mineralization were obtained under these conditions when 4‐AA was spiked into a municipal secondary effluent, showing a low influence of natural organic matter on PEF. The initially high acute toxicity determined using Artemia salina was largely diminished upon PEF treatment. Abstract : Treatment of 4‐aminoantipyrine by PEF : The application of a photoelectro‐Fenton process with a boron doped diamond anode under UVA illumination is highly efficient for the degradation and mineralization of this pollutant in municipal secondary effluent and provides decontaminated water without acute toxicity to Artemia salina .